RELATION OF CAREERS OF SCIENCE, ECONOMICS AND SOCIAL SCIENCES WITH THE ENTRANCE PROFILE OF STUDENTS - Rojas Torres, Luis (2014)
This study was carried in order to associate the careers of the Faculties of Sciences,Economics Sciences and Social Sciences of University of Costa Rica with a profile of incomeof its students, based on the average of admission and the option they selected thecareer to which entered. By an analysis of correspondence, it was noted that the careers atthe Faculty of Economics Sciences and Social Sciences are located in three groups distancedeach other, associated with different average levels of admission. Careers of the Facultyof Science are associated with each other and deviate from the profiles, indicating littleassociation with these; this faculty presents the case that Chemistry career is associatedwith a profile of income in second option. Also, it shows that in careers associated with high profiles, the percentage of non-registration is less than 12%, while in the low profilesit is exceeding 20%. These results provide a frame of reference on a problem of the collegeadmissions system associated with races with low income profiles.